The impact of Theileria parva infections and other factors on calf mean daily weight gains in smallholder dairy farms in Murang'a District - Gitau, G.K.; McDermott, John J.; McDermott, B.; Perry, Brian D. (Elsevier, 2001)
The association between mean daily weight gain, Theileria parva infections, clinical East Coast fever and other possible determinants of weight gain were examined in a longitudinal observational study that was conducted in cohorts of female calves from five agro-ecological zone (AEZ)-grazing strata. The strata were upper-midlands (UM) 1 zero-grazing, UM 1 open-grazing, UM 2 zero grazing, UM 4 zero-grazing and UM 4 open-grazing. In total, 225 calves on 188 smallholder dairy farms were visited within the first 2 weeks of life and thereafter at biweekly intervals up to the age of 6 months between March 1995 and August 1996. During each visit, the calves were weighed and other calf-management practices in the farm during the visit such as housing, feeding and tick control also were recorded. Other events such as morbidity and mortality between or during the visits were also recorded. The overall mean daily weight gains were 0.24-0.29 kg (S.D. = 0.17-0.22 kg) and were lower than the recommended targets for smallholder farms of 0.40-0.50 kg. The major tendency in variability of daily weight gains was due to visit-to-visit variation (especially in calves >3 months old). Differences in mean daily gains were associated with AEZ-grazing strata and calf-level factors that included breed of calf, calf sickness, incidence of ECF, feeding of milk, concentrate feeds and minerals and interaction between calf age and AEZ-grazing strata (P < 0.05). ECF and other calf sicknesses exerted a temporal effect on calf-growth at the height of illness and immediately after; calves later recovered the lost growth except where other factors such as poor calf nutrition prevailed. Improvement in calf-growth in Murang'a District is achievable and extension services should continue to target individual-calf-level management practices.